Using Scholarly Big Data in Assessing Contribution of National Expertise to Climate Change Knowledge; Case Study: Egypt - Hassaan, Mahmoud A. (Journal of Data Analysis and Information Processing, 2018)
Scholarly documents are generated on daily basis in varied formats. Google Scholar is one of the most popular open access web search engines that involves metadata of massive volume of varied scholarly literature that is generated autonomously and in high velocity. This means that Google Scholar data should be considered from Big Data perspective. Despite a growing literature on climate change in Egypt, there has never been a comprehensive survey of the literature produced by Egyptian researchers in the field. The paper in hand is intended to study and assess existing literature on climate change undertaken by Egyptian researchers available at Google Scholar. For this purpose, systematic mapping approach was utilized in this work. It was found that there were 189 research papers undertaken by Egyptian researchers on various climate change topics over a ten years period 2007-2017. Yet, about 33% of the produced literature was found to have been published in less reputable publications. Research papers undertaken by Egyptian researchers were found to be on the increase during this period. It was also found that the majority of the published research focused on specific topics such as agriculture and sea level rise, while disregarding a number of vital topics in the case of Egypt such as tourism, health and energy
Keywords: Big Data; Google Scholar; Egypt; Climate Change